ALCOHOL-BASED SEPTAL ABLATION OF INTERVENTRICULAR SEPTUM WITH CONTRAST ECHOCARDIOGRAPHIC CONTROL - A. G. Osiev; B. B. Gegenava; F. N. Paleev; N. M. Grigoryeva (Российский кардиологический журнал, 2017)
Alcohol septal ablation was introduced in 1994 as an alternative for surgical septal myectomy in patients with obstructive hypertrophic cardiomyopathy refractory to drug treatment. The procedure decreases symptoms of the disease creating targeted localized infarction focus of the upper part of interventricular spetum leading to increase of outgoing tract diameter, decrease of pressure gradient at the level of outgoing left ventricle tract and hypertrophy regression caused by overload. Such clinical improvement can be achieved in most cases. Main complication of the alcohol-based ablation — complete atrioventricular block with necessity, in some patients, of permanent cardiostimulator. Contrast echocradiography during alcohol septal ablation makes it to localize infarction, to use less amount of alcohol and, therefore, to decrease complications rate.